Analisis Kesenjangan antara Regulasi dan Praktik Pemenuhan Hak Anak dalam Konteks Perceraian - Eka Noviyani; Nency Dela Oktora; Mohammad Ilhamuna (Bulletin of Community Engagement, 2025)
This research discusses the gap between regulations and practices in providing children's rights in the context of divorce. This research aims to identify specifically where there are discrepancies between regulations and practices that occur in the field in efforts to fulfill children's rights after divorce. Apart from that, this research also aims to understand the impact or impact of this gap on the welfare and rights of children after divorce. This includes various risks faced by children who are victims of divorce, both in terms of physical, mental and social welfare. The research method used is a qualitative approach with data collection through semi-structured interviews and documentation. The research results show that the main problems include uncommitted parents, lack of family support, quality time, negative societal stigma, and children not being given a proper education. Factors causing this gap include economic conditions, responsibility, communication, intervention from other parties, the double burden carried and the low level of parental education. The implications of this exception between regulations and practice alleviate the child's condition. These implications include promiscuity, bad behavior, lack of affection, and also not having a role model in their life, which in the end can hinder a child's development.